Assistance in The Collation and Management of Waqf Into a Productive Waqf at The Hidayatullah Islamic Boarding School, Manyar, Gresik - Tri Wahyudi Ramdhan; Moh Holil Baitaputra; Bahrul Ulum; Mufaizin Mufaizin (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2023)
In addition to being a means of enhancing and developing self-quality, community development aims to increase the independence of both individuals and groups. It is strongly anticipated that community organizations will exist and oversee the accomplishment of institutional goals; nevertheless, their human resources must possess the flexibility to quickly seize any presented chances. In order to achieve strategic and sustainable goals where the principle of benefit will return to the community/ummah, waqf serves as a middleman for those who have more money to donate to community projects. This is in addition to the fact that waqf charity is itself a religious command.So the purpose of this service is to provide training and assistance on how to manage waqf money and waqf assets properly and productively according to the muwakif's objectives. This waqf collection and management assistance is carried out using the counselling method through several stages, including, 1) Activity programme planning; 2) Implementation of the activity plan 3) Implementation of activity evaluation and reporting. The goal of this help is to manage waqf funds efficiently and effectively while also accelerating the rise of waqf earnings. Senior students, Pesantren administration, and Baitul Wakaf Hidayatullah Gresik management participated in this exercise..